Sharia Compliance in Manure Trade: A Case Study of Sellers’ and Buyers’ Knowledge in Pedekik Village - Sri Wahyuningsih (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study analyzes the implementation of sellers’ and buyers’ knowledge of the pillars of buying and selling manure in Pedekik Village from an Islamic economic perspective. In Islamic transactions (muamalah), buying and selling must meet valid legal requirements to ensure fairness, transparency, and blessings. The research employs a qualitative case study approach using interviews, observations, and documentation. Research subjects include six sellers and five buyers of manure. The findings show that most participants possess limited understanding of Islamic legal provisions, particularly concerning the validity of the transaction object. Unprocessed manure, classified as impure (najis), is frequently traded without proper processing, violating Islamic commercial law. Some actors—especially those with religious or agricultural education—understand that manure must undergo fermentation before it is lawful to trade. This disparity reflects a lack of access to Islamic education, insufficient religious guidance, and minimal entrepreneurial training aligned with sharia. Consequently, many sale and purchase practices remain inconsistent with Islamic principles. From an Islamic economic standpoint, manure may only be sold if it offers clear utility and meets requirements of purity and lawful ownership. The study highlights the need for community education and structured training programs to improve shariacompliant commercial awareness. Collaboration between local authorities, religious leaders, and agricultural extension workers is essential to strengthen knowledge of Islamic economic ethics. Enhancing understanding of valid transactions will help ensure future trade practices in Pedekik Village reflect justice, mutual benefit, and the spirit of halal commerce.Keywords: Sale and Purchase, Manure, Islamic Economics, Community Knowledge, Transaction Terms.